Isolation and Characterization of Lewis Base Stabilized Monomeric Parent Stibanylboranes. Issue 44 (4th September 2015) - Marquardt, Christian; Hegen, Oliver; Hautmann, Matthias; Balázs, Gábor; Bodensteiner, Michael; Virovets, Alexander V.; Timoshkin, Alexey Y.; Scheer, Manfred
Abstract The synthesis of the Lewis base stabilized monomeric parent compound of stibanylboranes, "H2SbBH2", is reported. Through a salt metathesis route, the silyl‐substituted compounds (Me3Si)2SbBH2⋅LB (LB=NMe3, NHCMe) were synthesized as representatives of derivatives with a SbB σ bond. Under very mild conditions, they could be transformed into the target compounds Me3N⋅H2BHSbBH2⋅NMe3 and H2SbBH2⋅NHCMe, respectively. The products were characterized by X‐ray structure analysis, NMR spectroscopy, IR spectroscopy, and mass spectrometry. DFT calculations give further insight into the stability and bonding of these unique compounds.